IMPLEMENTASI STRATEGI OE3R (ORIENTASI-EKSPLORASI-EKSPLANASI-ELABORASI-REFLEKSI) PADA PEMBELAJARAN KIMIA TOPIK PENYETARAAN REAKSI REDOKS - sukrawati arni (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2022)
Chemistry is a science based on inquiry; therefore it is called inquiry-science. Chemistry learning should also be done through an inquiry basis. This study aims to describe the implementation of the OE3R strategy on the balancing redox reactions material and obtain student responses towards the OE3R strategy. Learning must of course work in harmony with the characteristics of students, learning facilities, and learning environment. The concept of OE3R (Orientation-Exploration-Explanation-Elaboration-Reflection) is an innovative effort of inquiry-based chemistry learning strategic model. In this study, the development of an OE3R strategy was conducted at MAN Kota Batu in the academic year 2021/2022 for chemistry learning with the topic of balancing redox reactions. The research method used is descriptive quantitative. The description of implementation is obtained from observation during learning, while the student's response is obtained by collecting responses through a questionnaire. The implementation of the OE3R strategy is carried out on the students of MAN Batu with a total of 60 students. The results of this study indicate that the students gave a good response, mostly (85%) students agree that learning with the OE3R strategy can be used in chemistry learning, especially the topic of balancing redox reactions. Students feel that learning is meaningful and expect the OE3R strategy to be applied to other chemistry materials.